Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1109/tasc.2012.2187291
|View full text |Cite
|
Sign up to set email alerts
|

Current–Time Characteristics of Resistive Superconducting Fault Current Limiters

Abstract: Superconducting fault current limiters (SFCLs) may play an important role in power-dense electrical systems. Therefore, it is important to understand the dynamic characteristics of SFCLs. This will allow the behavior of multiple SFCLs in a system to be fully understood during faults and other transient conditions, which will consequently permit the coordination of the SFCL devices to ensure that only the device(s) closest to the fault location will operate. It will also allow SFCL behavior and impact to be tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…Starting with the 1D analysis, despite than these models cannot give account of the electromagnetic or thermal response inside of the elements conforming a SFCL, neither study their detailed structure, the SFCL can be simulated into an equivalent electrical circuit dealing with all kinds of short-circuit failures, as a single non linear resistor obeying the E − J power law, E = E 0 · (J/Jc) n , for describing the superconducting state. Into this framework, most of the models have been developed in terms of the time-domain transient analysis method, customarily embedded by simulation packages such as: ATP/EMTP [39], PSCAD/EMTDC [40], and MATLAB/Simulink [41]. Proprietary packages with onpurpose advanced features for thermal transient analysis have been also developed under this scheme [42]- [43].…”
Section: Numerical Models and Simulation Methodsmentioning
confidence: 99%
“…Starting with the 1D analysis, despite than these models cannot give account of the electromagnetic or thermal response inside of the elements conforming a SFCL, neither study their detailed structure, the SFCL can be simulated into an equivalent electrical circuit dealing with all kinds of short-circuit failures, as a single non linear resistor obeying the E − J power law, E = E 0 · (J/Jc) n , for describing the superconducting state. Into this framework, most of the models have been developed in terms of the time-domain transient analysis method, customarily embedded by simulation packages such as: ATP/EMTP [39], PSCAD/EMTDC [40], and MATLAB/Simulink [41]. Proprietary packages with onpurpose advanced features for thermal transient analysis have been also developed under this scheme [42]- [43].…”
Section: Numerical Models and Simulation Methodsmentioning
confidence: 99%
“…However, in order to attain a more precise validation of the SFCL protection scheme regarding safety operation and power stability conditions, the recovery time of the SFCL cannot be assumed as an ad hoc parameter. Therefore, besides the exponential model, we have also studied the impact of considering the temperature dependence of the flux-creep and flux-flow regimes describing the time-dependent quench of the superconducting material, such that the averaged instantaneous temperature of the SFCL, T (t), can be calculated by solving the classical heat transfer equation [21]. Theis thermal subsystem is then coupled to the electrical module of the power system, as a temperature dependent E − J power law of similar structure to the one proposed by Lacroix and Sirois in Ref.…”
Section: Power System Configuration and Sfcl Schemementioning
confidence: 99%
“…However, the reductions in SFCL weight which are required to increase power density ratings from ≈ 4 kW/kg of TRL 5-6 devices in 2013 to the 4000 kW/kg mentioned in the same study 39 , imply that SFCLs are not likely to feature in any FMS for N+1 or N+2 aircraft. Whilst naval SFCLs currently under development 40,41 are expected to reduce weight and volume compared to terrestrial systems, it is expected that this technology will need to be developed and demonstrated in naval systems before being adapted and further reduced in size for a hybrid aircraft.…”
Section: Power Density Of Sfclsmentioning
confidence: 99%